Visitors’ satisfaction level at Sunway Lagoon Theme Park / Wan Ilyuni Amilla Wan Mohd Rosdi - Wan Ilyuni Amilla, Wan Mohd Rosdi (2019)
Theme parks are important for tourism attraction. Every theme park need to take a considerations of visitors’ satisfaction who visit the theme park. It is because the visitors make the theme parks are still operating. Realizing that the condition of the theme parks is uncomfortable for visitors and it is lack of facilities. The aim of the research is to know the visitors’ satisfaction level at Sunway lagoon theme parks. The purpose of this study are identify facilities and game rides provided at theme park, determine the user’s satisfaction level on dry park and wet park, determine the user’s satisfaction level of facilities at theme park and recommend solution to improve visitors’ satisfaction level at theme park. The scope of this research will be focuses at Sunway Lagoon theme park. These theme park was selected because it is the largest theme park in Malaysia. The wet park and dry park were provided at Sunway lagoon. The study will be focused on safety, cleanliness, comfort and facilities. To achieve the research objectives, the data of this research is gathered through questionnaires and observations. Questionnaires will be distributed among the visitors that visit Sunway Lagoon theme park. The collected data will transfer to SPSS software which the outcome has been in the form of table and bar chart. The data by observation are observe the facilities and game rides that provided.